Stabilizing the Excavation Materials to be used in Fill Layers - Ali Sabbagh Moghadam; Navid Hadiani (Salehan Institute of Higher Education, 2018)
Daily increase in the amounts of soil and wastes produced by excavation and demolishing of the old buildings in the urban worn out textures has caused great problems in large cities. The environmental issues due to the irrelevant and non-technical disposal of waste materials have attracted attention of researchers with the aim of recycling and use of these materials in the civil and construction activities. Old buildings constitute a significant portion of Sharestan Razavi Blvd in Mashhad which after demolishing of these buildings the area in this section is covered by the backfill materials and those remained from the demolishing of the buildings. In this research, maximizing use of the available materials and minimizing the transportation work as an execution order have been under focus of attention. Also through performing various tests, the possibility of recycling, stabilizing and implementing these materials at underlying layers of Sharestan Razavi Blvd has been evaluated and the results are presented.